Evaluation of various varieties of peas as raw material for deep processing - V. G. Goldstein; L. P. Nosovskaya; L. V. Adikaeva; V. A. Kovalenok (Аграрная наука Евро-Северо-Востока)
The article provides an overview of the criteria for choosing pea varieties to evaluate economically valuable traits. For the effective use of peas as raw materials for deep processing, two directions can be considered: a joint increase in the content of protein and starch or the choice of varieties with the required indicators. The results of laboratory studies of processing for starch and protein isolate of 37 variety samples of peas from the collection of the Federal State Budgetary Scientific Institution «Federal Scientific Center of Legumes and Groat Crops» are presented. As evaluation criteria determining high technological properties, providing the most complete extraction of starch and protein isolate there have been selected coefficients of extraction of these components. When selecting a variety of peas, it is also necessary to consider the physicochemical properties of starch, which depend on the mass fraction of amylose. According to the results obtained, the most promising varieties for the processing of grain into starch and protein isolate are Orlovchanin, Alla, Rodnik, Sibirsky 1, Pharaon, Jaguar, Sophia. The most efficient extraction of the main processed products ‒ protein isolate and starch is established for the variety Alla, protein extraction coefficient 81.2 %, starch 90.6 %. Among the wrinkled pea varieties for industrial processing, the Amius 1241 breeding line is the most interesting, with protein isolate and starch extraction coefficients of 70.3 and 69.1 % and a mass fraction of amylose in starch of 81.5 %. It is found that the mass fraction of starch and protein in pea grains does not correlate with the extraction coefficients of protein and starch isolate during processing by two-stage extraction of protein from pea flour using the alkaline method. When processing wrinkled pea varieties, there are difficulties in separating the starch and residual protein undissolved in alkaline medium, since these pea varieties are found to have complex starch granules, which are easily crushed into small irregular and polygonal granules. In smooth pea varieties, the starch granules are oval in shape with a high percentage of large size and therefore there are no problems with separation of the starch-protein suspension. The dependence of viscosity of 3.0 % pea starch paste on the mass fraction of amylose in pea starch has been determined. The choice of pea variety for processing makes it possible to produce starch that has lifetime modification, i.e., that has the required physical and chemical properties and resistance. In addition, depending on the choice of pea variety, it is possible to predict the yield of isolate and protein concentrate.